HARMONI KOMUNIKASI LINTAS AGAMA BERBASIS EKONOMI DAN RITUAL: STUDI FENOMENOLOGI PADA KOMUNITAS MUSLIM DAN HINDU DI DESA LINGSAR, KABUPATEN LOMBOK BARAT - Kadri Kadri (KOMUNITAS, 2022)
The two religious communities are able to share the available space as a work place, use the crops from farming for the performance of rituals together and utilize the Lingsar Gardens retribution money in turn. They utilize the public facilities in Lingsar Gardens together without conflict. The Muslim and Hindu communities also utilize the ritualistic facilities available in line with their purpose. The Hindu community pray in Gaduh Temple and at the same time the Muslim community perform cultural and religious rituals in a place that is available in the Lingsar Kemaliq complex.They also use the same place to perform the rice cake war as a united cultural ritual in an atmosphere of joyfulness and spirit of togetherness. The high tolerance of the Muslim and Hindu communities enables them to succeed in sharing the space at Lingsar Gardens while at the same time making this a pleasant public space.